Risk of Psychosis in People of Irish and Chinese Ethnicities in Yorkshire - Sarthak Sinha; Tariq Mahmood; Alastair Cardno; Emi Obode (BJPsych Open)
Aims: Studies have shown an elevated risk of psychosis among migrants and ethnic minorities, but there has been little investigation of risks for Irish and Chinese ethnic groups in the UK. The aim of this study is to investigate the risk of first-episode psychosis in White Irish and Chinese ethnic groups compared with the White British population in West Yorkshire.